1982
DOI: 10.1159/000241611
|View full text |Cite
|
Sign up to set email alerts
|

Echinocytic Sensitivity and Deformability of Human Newborn Red Cells

Abstract: Echinocytic red cells are present in the peripheral blood of normal human newborns in small but significant numbers. This is in contrast to normal adults in whom no echinocytes are found in peripheral blood. In addition, red cells from newborns have increased susceptibility to echinocyte transformation induced by naturally occurring phospholipid lysolecithin. The mechanism for this increased susceptibility does not appear to be related to the lipid composition of these cells. Cellular deformability of red cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1985
1985
1995
1995

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Those features that might affect their use include a predominance of Hb F with a higher oxygen affinity, a shortened iri vivo life-span, increased proportion of morphologic abnormalities, greater susceptibility to lipid peroxidation, altered membrane lipid fluidity, and more labile ATP levels (26)(27)(28)(29). Ultimately, clinical studies evaluating in vivo posttransfusion red cell survival will determine whether transfused autologous placental blood is as satisfactory as donor blood.…”
Section: Discussionmentioning
confidence: 99%
“…Those features that might affect their use include a predominance of Hb F with a higher oxygen affinity, a shortened iri vivo life-span, increased proportion of morphologic abnormalities, greater susceptibility to lipid peroxidation, altered membrane lipid fluidity, and more labile ATP levels (26)(27)(28)(29). Ultimately, clinical studies evaluating in vivo posttransfusion red cell survival will determine whether transfused autologous placental blood is as satisfactory as donor blood.…”
Section: Discussionmentioning
confidence: 99%
“…This should accelerate the shape transfornations in neonates if the incorporation rate is the same in neonates and adults. It has also been shown that neonatal erythrocytes are sensitive to slightly lower concentrations of LPC after 5 min of incubation (Coulombel et al 1982), while the proportion of cupped cells with CPZ after 15 min of incubation is the same in the cells of neonates as in the case of adults, and that found with high CPZ concentrations is even higher (Matovcik et al 1985).…”
Section: Number Of Cells Counted Varied From 53 To 180 the Times Reqmentioning
confidence: 99%
“…Studies on the deformability from fetal erythrocytes have been controversial [1,2,4,8,11,16,18], because it is considered that obtained data depend on the difference of measurement methods. It should be stressed that we hypothesize that deformability of fetal erythrocytes is increased for the reason as mentioned above.…”
Section: Introductionmentioning
confidence: 99%